Automated IFC-based building information modelling and extraction for supporting value analysis of buildings. Issue 4 (3rd July 2020) - Zhang, Lu; El-Gohary, Nora M.
Abstract: The value of a building is quantified and analyzed based on its properties. Building information modelling (BIM), which allows for rich representation of building properties, creates an opportunity to conduct value analysis automatically. To support automated value analysis, there is a need to identify and extract value-specific design information (i.e. relevant and sufficient information for value analysis) from a BIM model and utilize this information to enable value analysis. To address this need, this paper proposes a method for value-focused modelling and extraction of design information from an Industry Foundation Classes (IFC)-based BIM model. The method includes two primary elements: (1) extending the IFC schema to include the additional entities and property sets that are needed to represent the necessary information for conducting value analysis; and (2) extracting the target design information from an IFC-based BIM instance model. The information extraction method was tested in extracting target design information from two BIM models. A 100% precision and recall was achieved, which indicates that all and only the necessary information was extracted. This research contributes to the body of knowledge by offering an extended IFC schema and a value-specific BIM information extraction method, which together support automated value analysis of buildings.